Manutenção centrada em confiabilidade em um robô de uma linha de estampagem: um caso de estudo - Tertuliano, Davi Ferreira (2012)
This study had as main objective to propose a maintenance plan for components of critical systems of stamping line robot using the methodology of Reliability Centered Maintenance (RCM). To reach this objective was developed a research of an applied constitution, with qualitative approach to the problem, exploratory about the objectives, using the techniques of bibliographical, documentary and field. From the study, using the tools of the RCM, it was possible to propose a maintenance plan for the most critical subsystems of the robot and even suggest some actions, to be implemented in companies, with regard to their maintenance processes.